Experience with Combined Vaccination against Pertussis, Diphtheria, Tetanus and Influenza in Workers with Occupational Respiratory Disease Hazard - N. A. Roslaya; N. A. Lugovskaya; I. O. Kholopov (Эпидемиология и вакцинопрофилактика)
Relevance. Respiratory diseases, flu and pertussis, in particular, are common causes of temporary disability at work place. Pertussis is the second most common infectious disease by incidents increase in the Russian Federation. Combined immunization is found to be an efficient method to prevent infections at work place.Objective. Research objective is to prove safety of combined influenza and the diphtheria-tetanus-pertussis vaccines for people with occupational hazard of respiratory diseases.Materials and methods. We have studied the vaccination process in 257 adults with 2-nd and 3-rd health groups. We evaluated post-vaccination reactions, their localization, severity, time onset, and duration. We identified two groups with weaker and stronger side effects after vaccination. We determined typical parameters of the vaccination process.Results. 50% people in examined group showed adverse reaction. Symptoms were weak as a rule and lasted up to 4 days mostly. 29 people (11%) had more severe and long reaction. 6 patients (2%) required supportive care, 2 (0.8%) showed severe symptoms lasting from 2 to up to 5 days.Conclusion. The application of influenza vaccination combined with diphtheria, tetanus and pertussis vaccinations simultaneously have demonstrated that it is safe to use in adults at risk of exposure for respiratory diseases at workplace. Minor side effects do not pose a health threat, and can be completely prevented.